Penglipuran Traditional Village, Kubu Village, Bangli Regency, Bali as a Cultural Tourism Village Based on Local Wisdom and Creative Economy - I Wayan Wesna Astara; I Nyoman Putu Budiartha; I Wayan Rideng; I Nyoman Gede Sugiartha (Law Doctoral Community Service Journal, 2022)
The traditional village of Penglipuran Kubu, Bangli Regency has the potential as a tourist village. The potential of culture and natural resources can be managed into a tourism village product by collaborating with culture, natural resources, human resources, and tourism village management. In order for the management of the tourist village to be sustainable, the management strategy and laws related to the tourist village become the manager's reference. It was found that the management of the tourist village is still weak. The problem of tourist villages can use the absorption method from research results found both from service research results and from other researchers to be expected to provide solutions to the Penglipuran indigenous peoples who manage tourist villages. The role of the government after the development of the Penglipuran tourist village has decreased, it should remain a dynamist for the Penglipuran indigenous people. The methods used in legal issues in the management of tourism villages, focus group discussions (FGD), mentoring, lectures on legal science, dissect cases related to tourism village institutions, find potential strategies for local wisdom to strengthen tourism villages based on local wisdom, ensure continuity Penglipuran tourism village, assisting tourism awareness groups in managing tourism villages in growing the creative economy. The results of the service show that the Penglipuran tourist village, the lands that are used as tourist village objects are customary lands (Tanah Ayahan Desa). There is a legal problem that AYDs land is certified by Krama Adat. Another problem, which needs legal assistance, and legal counseling that the Penglipuran tourist village is managed by a tourism village management business entity, then a new problem arises with the Regional Regulation Number 4 of 2019 concerning customary villages, that Traditional Villages have Utsaha, to be managed by BUPDA (Baga Utsaha Padruwen Desa adat) based on customary law.